The Legal Position of the Security Unit in the Perspective of Labor Law: Kedudukan Hukum Satuan Pengamanan dalam Perspektif Hukum Ketenagakerjaan - Teguh, Pribampudi; Mustakim (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine the legal position of security guards in relation to labor law aspects. This research is a normative legal research with a concept and statutory approach. The results of the study confirm that the legal position of a security guard in employment law is that in terms of duties and authorities, a security guard actually carries out the duties of the police, but in terms of rights and obligations in general, such as those related to wages, leave, overtime and so on, they should be based on labor provisions as stipulated in the Labor Law and the Job Creation Law. Regarding the guarantee of employment rights for security guards in the perspective of labor law based on the principle of ejusdem generis in general it can be equated with rights for workers in general, such as: the right to adequate wages, the right to leave, the right to health insurance, the right to severance pay, as well as the right to legal protection. However, there are rights that need to get special arrangements related to security guards in their position as special workers such as the right to associate and assemble which need to be further regulated through government regulations and presidential regulations which contain: the position of independent security guards, especially security guards, rights and obligations, as well as efforts and legal mechanisms. Highlights: Dual Role: Security guards perform police duties and have labor law rights. Employment Rights: Guards' rights align with general workers. Special Regulations: Specific rights need further government regulation. Keywords: labor law, security guard, SATPAM